Internalization of Entrepreneurial Character Values in Culinary Skills Learning at SMALB Tunarungu (Phenomenology Study in SLB Negeri of Bandung City) - Saefullah, Aep; Sauri, Sofyan; Malihah, Elly (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
The shortage of deaf engagement in both business and entrepreneurship sectors is an issue for the education aspect, specifically concerning independence and prosperity achievement. The purpose of this research is to disclose the internalization process of entrepreneurial character values in culinary skills learning at SMALB Tunarungu. This study was conducted by qualitative method with a phenomenological approach, aimed to reveal and describe existing phenomena through a series of procedures, such as 1) preliminary study, 2) data collection through observation, interview, documentation, and Focus Group Discussion FGD, and 3) data analysis. Based on the existing phenomenon, the results of this study reveal that 1) entrepreneurial character values were developed in planning learning activities as referred to in the curriculum of the education unit that had been set by the school; 2) the performed learning activity of culinary skills applied entrepreneurial character values. It was by integrating into the learning process with appropriate model, media, and approach with characteristics of deaf students; 3) evaluation in the internalization of character values used provisions in the used curriculum; and, 4) constraints on the implementation of entrepreneurial character internalization relied on an understanding of the language concept, especially in interpreting character values, which were abstract for deaf students.